Statystyka i ekonometria realizowane na kierunkach ekonomicznych w świetle obowiązujących standardów nauczania - Parlińska, Maria; Pietrzykowski, Robert (Statistics and econometrics at the economical studies in the frame of standards of education, 2011)
The paper demonstrates the problem and range of quantitative subjects (statistics and econometrics) on Faculty of Economic Sciences, University of Life Sciences in Warsaw. The introduction presents Microsoft Excel, a commercial spreadsheet application, which gained a positive opinion of the students who felt that, in addition to econometrics, they even learnt to use the tool used not only in econometrics or statistics. The introduction of the new law on higher education, which is to abolish the teaching standards, may result in reducing the hours of statistics, econometrics, mathematics and others
Didactics of Mathematics, 2011, Nr 8 (12), s. 113-118
Keywords: education; econometrics; statistics; quantitative subjects